Metal Homeostasis in Pathogenic Streptococci - Madeline S. Akbari; Kelly S. Doran; Lindsey R. Burcham (Microorganisms, 2022)
Streptococcus spp. are an important genus of Gram-positive bacteria, many of which are opportunistic pathogens that are capable of causing invasive disease in a wide range of populations. Metals, especially transition metal ions, are an essential nutrient for all organisms. Therefore, to survive across dynamic host environments, Streptococci have evolved complex systems to withstand metal stress and maintain metal homeostasis, especially during colonization and infection. There are many different types of transport systems that are used by bacteria to import or export metals that can be highly specific or promiscuous. Focusing on the most well studied transition metals of zinc, manganese, iron, nickel, and copper, this review aims to summarize the current knowledge of metal homeostasis in pathogenic Streptococci, and their role in virulence.